The effect of Cu concentration in soil and phosphorous fertilizer on plant growth and Cu uptake by Brassia juncea L. grown on contaminated soils - Cu, Nguyen Xuan (VNU Journal of Science: Earth and Environmental Sciences; Vol 24 No 3, 2008)
Abstract